Survey of the Ketcham reaction for series of furan-substituted thiazolo[5, 4-d]thiazoles. (4th June 2021) - Tokárová, Zita; Eckstein-Andicsová, Anita; Balogh, Róbert; Tokár, Kamil
Abstract: Available online-Thiazolo[5, 4- d ]thiazoles/TzTz are active moieties in photovoltaic and optoelectronic materials. Initial TzTz synthesis relies on the Ketcham reaction that, however is ultimate possess number of challenges. Along with practical imperfections, most of the disadvantages arise from uncertain reaction proceeding. Our study have focused on more detailed reaction process that is accompained with the formation of stable intermediates. Structures of achieved side products were determined and correlated with the mechanism suggesting to more complex behaviour. Physico-chemical properties combined with theoretical DFT approaches have proved that the thiazolo[5, 4- d ]thiazoles are suitable to be incorporated as a parts of particular organic devices. Graphical abstract: Image 1 Highlights: synthesis of the representative derivatives focusing in more complex on the Ketcham reaction proceeding. The formation of the possible side products are presented. Explanation of the possible reaction mechanism.